Application of the Orem Self Care Theory in the Assessment of Mothers with Severe Preeclampsia with Electrolyte Disorders: Case Study - Irma Rachmawati; Windy Natasha; Ermiati Ermiati; Restuning Widiasih (GLOBAL HEALTH SCIENCE GROUP, 2024)
One of the causes of maternal death is uncontrolled complications of severe hypertension. In preeclampsia, the risk to the fetus is very high, such as delayed intrauterine growth, prematurity and intrauterine death. Signs and symptoms of severe preeclampsia should be used as an